Alcohol abuse and its impact on food security in Igembe South Sub-county (African Journal of Science, Technology and Social Sciences, 2022)
Food security in Kenya has worsened substantially over the last 30 years, with high population and increasing food demand consistently exceeding modest agricultural production growth.  There is a very strong link between agricultural productivity and alcohol consumption especially in the rural areas. The purpose of this study is to understand the demand patterns of alcohol and its impact on food security in Igembe South Sub-County. Cross sectional descriptive survey design was used to undertake the study. The target population was all the households in Igembe South Sub-County. The sample size of the study was 384 respondents. The study employed three sets of data collection instruments. Interviewer-administered structured questionnaire, observation checklist and key informant interview guide. Qualitative and econometric data analyses was carried out in this study to provide a deeper understanding of alcohol households’ demand and how it affects the food security situation in Igembe South-Sub County. The results indicate that Alcohol consumption by the household head was associated with an increase in food insecurity, a statistically significant effect with an odds ratio of 1.593(95% CI 1.152 to 2.035, Wald χ2(1) = 50.015, p ˂0.05. An ordinal regression model was highly statistically significant with P˂0.005 and all the socio-economic variables being significant and Nagelkeke pseudo R-Square being 0.75. Patterns of alcohol consumption affected food security in the household. This was statistically significant in its predictive ability X2 (11) = 140.834, p < .01. Nagelkerke R-Square for the model is 0.737. The study concludes that alcohol consumption can cause serious food security problems in the household and it recommends that the government needs to develop and implement firm policies for the control of sale and consumption of alcohol so as to help reduce alcohol intake among the general populace. The study also recommends that media also needs to play its part by promoting campaigns and messages that emphasize the risks involved in the use of alcohol.
Keywords: Alcohol abuse; Food Security